POTENSI CUKA BAMBU PT. BUKIT ASAM PELABUHAN TARAHAN UNTUK MENGURANGI PENGGUNAAN PUPUK KIMIA PADA BUDIDAYA TANAMAN PAKCHOY (Brassica rapa L.) - Rizka Novi Sesanti; Dianto Sudrajat; Fahri Ali; Reny Mita Sari (Politeknik Negeri Lampung., 2021)
Continuous use of chemical fertilizers can reduce soil fertility and decrease crop quality. To maintain the soil fertility and increase the crop production, can be done by combining chemical fertilizers with organic fertilizers, so the use of chemical fertilizers can be reduced by being substituted by organic fertilizers. Liquid smoke (bamboo vinegar) is one of natural materials which is potential to be liquid organic fertilizer. The research on the potential of bamboo vinegar is mostly directed at its function as a food preservative and vegetable pesticide, however, the bamboo vinegar also potential as an organic material that can reduce the use of chemical fertilizers in plant cultivation. This study aims to determine the potential of bamboo vinegar as an organic material that can reduce the use of chemical fertilizers in the cultivation of pakchoy plants. This study use factorial 5 x 2 Randomized Block Design (RAK) with 3 replications. The first factor is the amount of bamboo vinegar and NPK; 100% bamboo vinegar, 75% bamboo vinegar + 25% NPK, 50% bamboo vinegar + 50% NPK, 25% bamboo vinegar + 75% NPK, and 100% NPK. The second factor is the frequency of fertilization; once and twice application. The results showed that the use of bamboo vinegar with 100% dose of concentration without the addition of NPK (10 ml/liter/plant) was able to produce the same height and number of leaves with the use of 100% NPK (2 g/plant). The use of bamboo vinegar + NPK at 50% dose of concentration (5 ml / liter / plant + 1 gram / plant) at one time frequency of fertilization and the use of bamboo vinegar at 75% dose concentration (7.5 ml / liter / plant) + NPK 25% (0.5 gram/plant) at twice fertilization frequency was able to produce wet weight of canopy which has no differences with the use of 100% NPK (2 grams/plant). The application of bamboo vinegar can reduce the use of NPK chemical fertilizers in pakchoy cultivation depends on the frequency of fertilization.